If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 7) = 6x + -39 Reorder the terms: -3(7 + x) = 6x + -39 (7 * -3 + x * -3) = 6x + -39 (-21 + -3x) = 6x + -39 Reorder the terms: -21 + -3x = -39 + 6x Solving -21 + -3x = -39 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -21 + -3x + -6x = -39 + 6x + -6x Combine like terms: -3x + -6x = -9x -21 + -9x = -39 + 6x + -6x Combine like terms: 6x + -6x = 0 -21 + -9x = -39 + 0 -21 + -9x = -39 Add '21' to each side of the equation. -21 + 21 + -9x = -39 + 21 Combine like terms: -21 + 21 = 0 0 + -9x = -39 + 21 -9x = -39 + 21 Combine like terms: -39 + 21 = -18 -9x = -18 Divide each side by '-9'. x = 2 Simplifying x = 2
| -10+9k=62 | | 5x^2-14x-76=0 | | x-.10x=150 | | 7(8x+8)=56x-1 | | 13-50=20(5x-9x)+6x | | -1-(-12)= | | 8t/6 | | 2*15/7 | | cbrt(2x-3)=3 | | 11-12x=-11s | | 4(-3x)+y=2 | | 0.166666667x=4 | | 15y+9x=30 | | 8y+7=9y-1 | | 52=4(s-67) | | 5-5cosx=0 | | 9*b+4=7 | | -26-49= | | -8(-3-2n)=104 | | -7+2(1-5s)=35 | | 9*-b+4=7 | | p/3=1/8 | | 13y-7y=18 | | 81/9*(10-1)=x | | (10i)/(6-5i) | | k^2+10k-65=-9 | | 10y+32=92 | | 8-9=39 | | 3x^2+18x-43=5 | | Y-2=-1/5(x-5) | | -4-(-5)/7=13 | | -9(z-97)=45 |